2020
DOI: 10.1002/smll.202002169
|View full text |Cite|
|
Sign up to set email alerts
|

Nanopore Targeted Sequencing for the Accurate and Comprehensive Detection of SARS‐CoV‐2 and Other Respiratory Viruses

Abstract: The ongoing global novel coronavirus pneumonia COVID‐19 outbreak has engendered numerous cases of infection and death. COVID‐19 diagnosis relies upon nucleic acid detection; however, currently recommended methods exhibit high false‐negative rates and are unable to identify other respiratory virus infections, thereby resulting in patient misdiagnosis and impeding epidemic containment. Combining the advantages of targeted amplification and long‐read, real‐time nanopore sequencing, herein, nanopore targeted seque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
210
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(215 citation statements)
references
References 48 publications
2
210
0
1
Order By: Relevance
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 47%
“…We observed that the RT-LAMP assay was less sensitive and informative than multiplex PCR-based NGS in our study and other literature (20)(21)(22)(23)(24). NGS is a robust tool for obtaining extensive genetic information, allowing LOD values as low as 10 copies/ml for SARS-CoV-2 and serving as a reference test for COVID-19, especially for those challenging samples with a low viral content (2,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 47%
“…The CRISPR/Cas technology is characterized by high specificity, high precision, high efficiency, and simple and fast operation. 38,59 0.5-1 h 29,111,112 0.5-1 h 38,40,113 Sensitivity N. A. † 73%-86% 32,33,114 81% -100% 38,40,115 Specificity 100% 116 86% -100% 32,33,114 99% -100% 38,40,115 Advantages Unknown virus identification, viral mutation and evolution screening.…”
Section: Crisprmentioning
confidence: 99%
“…Wang et al, developed a nanopore targeted sequencing (NTS) method, combining the advantages of target amplication and long-read, real-time nanopore sequencing, to be used for diagnosing COVID-19 and simultaneously detecting other common respiratory viruses and mutated nucleic acid sequences, within 6-10 h. Parallel testing of 61 nucleic acid samples from suspected COVID-19 cases with commercial RT-PCR kits and the proposed NTS method, showed the NTS method was more sensitive for SARS-CoV-2 detection and identied more positive cases. 21 Although the accuracy of gene sequencing to detect SARS-CoV-2 is high, there are limitations in its clinical application due to testing duration, high cost, and complex equipment. Finally, with the ongoing spread of COVID-19, genome sequencing has shied from initial virus identication to investigation of the origin and evolution of the SARS-CoV-2 virus.…”
Section: Nucleic Acid-based Detection Methodsmentioning
confidence: 99%